Silencing Quiet Quitting: Crafting a Symphony of High‐Performance Work Systems and Psychological Conditions - Agarwal, Promila; Kaur, Prabhjot; Budhwar, Pawan (Human Resource Management, 2025)
ABSTRACT A key question in the literature is how human resource management (HRM) practices influence quiet quitting (QQ), emphasizing the need for a more nuanced theoretical framework to explain its antecedents. This research applies the conservation of resources (COR) theory to delve into how high‐performance work systems (HPWSs) influence QQ through psychological conditions (i.e., psychological meaningfulness and availability). Based on a sample of 422 participants, the study reveals that HPWSs, psychological meaningfulness, and psychological availability each have a negative relationship with QQ. In addition, psychological meaningfulness and availability serve as mediating pathways through which HPWSs can mitigate QQ. The findings pave the way for further research on effective interventions and management practices that can create more fulfilling and productive work environments.